Chaos, resistant and pseudoresistant hypertension “Thousands of butterflies in the BP control system” - Yugar-Toledo, Juan Carlos; Dinamarco, Nelson; Rodrigues, Bruno; Moreno, Heitor (Journal of Cardiovascular Medicine and Cardiology, 2022)
In Cardiology, we classify hypertensive patients as resistant to treatment, pseudo-resistant, or hyperreactivity subjects, including the WCH (white-coat or masked hypertension). Compliance is another cause of failure in antihypertensive therapy. Hypertension is a complex clinical syndrome and many variables that interfere in BP depend on “The Theory of Chaos” and are not considered. We do not know how many variations the Chaos on BP levels can be. Still, as we have around 30% of “uncontrolled” patients, the Chaos and effects on BP regulation as taking part in this high rates of “uncontrolled” subjects. Chaos is a complicated issue to study, but multi-professional efforts must keep the attention to this relevant “cause” of hypertension. Finally, Chaos theory is well known and accepted in Maths, Economy, Philosophy, Meteorology, Ecology, and other areas of knowledge, but not in the Health area. Crescent attention to Chaos may help better understand some mechanisms and clinical expression of Chaos in pseudo-resistant hypertension and correlated hypertensive syndromes.